Enzymatic Versus Traditional Surgical Debridement of Severely Burned Hands: A Comparison of Selectivity, Efficacy, Healing Time, and Three-Month Scar Quality. Issue 4 (July 2017) - Schulz, Alexandra; Shoham, Yaron; Rosenberg, Lior; Rothermund, Irene; Perbix, Walther; Christian Fuchs, Paul; Lipensky, Alexandra; Schiefer, Jennifer Lynn
Abstract : Severe burns of the hands are extremely challenging, given their anatomic complexity and vulnerability. Although excisional debridement with autografting remains the standard of care (SOC), previous studies have shown that use of enzymatic debridement with bromelain (NexoBrid, EDNX) enables rapid, selective enzymatic debridement, preserving viable tissue. To date, only two studies accruing data on EDNX in this setting have been published. The current study was conducted to compare EDNX with traditional surgical debridement (TSD) of deep dermal and full-thickness hand burns. This single-center, controlled clinical trial included 40 patients, aged 18 to 76 years, with deep dermal burns of the hand. The first 20 patients were debrided surgically, and the other 20 patients were using EDNX for debridement. Therapeutic selectivity, time to complete debridement and healing, complications, and 3-month functional/esthetic outcomes were compared by group. EDNX (vs TSD) significantly reduced time to complete debridement after admission (0.95 day vs 7.750 days; P < .001) and treatments needed for complete debridement (1.05 vs 1.45; P < .001), improving burn depth evaluation (initially overestimated in 55% of EDNX-treated patients). The number of wounds requiring autografting was certainly reduced (15% vs 95%; P = .034), as was time to complete healing after first debridement (23.30 vs 32.00 days; P < .001), and early scar quality after 3 months was nearly equivalent, with only heightened local redness in the EDNX group ( P < .001). Compared with TSD, EDNX was superior in burn depth evaluation, tissue preservation, completeness of debridement, and wound closure. Scar quality after 3 months did not differ substantially.